The Social Construction of New Understanding Wali in Java - Masduki, Anwar (DINIKA : Academic Journal of Islamic Studies, 2016)
The social construction of sainthood lies in a broad-based understanding of Sufism and mysticism in Java. It appears in the way people recognize an individual as a saint in the real life; from fulfilling the role of Islamic propagators and the exercise of magical power as an extraordinary ability to do something. Nowadays, this understanding has apparently flourished, turning into new perceptions and understandings. The case of Gus Dur could be used as an example of the modern constructions of the sainthood in Java. Although there are widespread acceptances this sainthood, but this phenomena remains controversial and debatable. Therefore, this paper focuses on the social construction of new phenomenon called the Wali Sepuluh (the ten saints), to examine the issue of Gus Dur as the tenth saint and its impact on the realities of life in Tebuireng.KeywordsSainthood, social construction, and pilgrims